NOX4 is a major regulator of cord blood-derived endothelial colony-forming cells which promotes post-ischaemic revascularization. Issue 2 (1st April 2019) - O'Neill, Karla M; Campbell, David C; Edgar, Kevin S; Gill, Eleanor K; Moez, Arya; McLoughlin, Kiran J; O'Neill, Christina L; Dellett, Margaret; Hargey, Ciarán J; Abudalo, Rawan A; O'Hare, Michael; Doyle, Philip; et al.
Abstract: Aims: Cord blood-derived endothelial colony-forming cells (CB-ECFCs) are a defined progenitor population with established roles in vascular homeostasis and angiogenesis, which possess low immunogenicity and high potential for allogeneic therapy and are highly sensitive to regulation by reactive oxygen species (ROS). The aim of this study was to define the precise role of the major ROS-producing enzyme, NOX4 NADPH oxidase, in CB-ECFC vasoreparative function. Methods and results: In vitro CB-ECFC migration (scratch-wound assay) and tubulogenesis (tube length, branch number) was enhanced by phorbol 12-myristate 13-acetate (PMA)-induced superoxide in a NOX-dependent manner. CB-ECFCs highly-expressed NOX4, which was further induced by PMA, whilst NOX4 siRNA and plasmid overexpression reduced and potentiated in vitro function, respectively. Increased ROS generation in NOX4-overexpressing CB-ECFCs (DCF fluorescence, flow cytometry) was specifically reduced by superoxide dismutase, highlighting induction of ROS-specific signalling. Laser Doppler imaging of mouse ischaemic hindlimbs at 7 days indicated that NOX4-knockdown CB-ECFCs inhibited blood flow recovery, which was enhanced by NOX4-overexpressing CB-ECFCs. Tissue analysis at 14 days revealed consistent alterations in vascular density (lectin expression) and eNOS protein despite clearance of injected CB-ECFCs, suggesting NOX4-mediated modulation of host tissue. Indeed, proteome array analysis indicated that NOX4-knockdown CB-ECFCs largely suppressed tissue angiogenesis, whilst NOX4-overexpressing CB-ECFCs up-regulated a number of pro-angiogenic factors specifically-linked with eNOS signalling, in parallel with equivalent modulation of NOX-dependent ROS generation, suggesting that CB-ECFC NOX4 signalling may promote host vascular repair. Conclusion: Taken together, these findings indicate a key role for NOX4 in CB-ECFCs, thereby highlighting its potential as a target for enhancing their reparative function through therapeutic priming to support creation of a pro-reparative microenvironment and effective post-ischaemic revascularization.